1989
DOI: 10.2214/ajr.152.2.261
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of pulmonary nodules: comparison between standard and inverse digitized images and conventional chest radiographs

Abstract: We compared plain chest radiographs, standard (bones white) digitized images, and inverse-intensity (bones black) images to determine their ability to identify pathologically confirmed malignant pulmonary nodules. The images were digitized by using a photo-optical laser scanner and were displayed on a 1024 x 1024 x 8 bit system capable of operator-controlled magnification (2x or 4x) and nonlinear (logarithmic/exponential) contrast transformation in both standard and inverse-intensity modes. Receiver-operator c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
1
8

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 1 publication
6
28
1
8
Order By: Relevance
“…By comparing the ability to identify pulmonary nodules on conventional plain chest radiographs, standard (bones white) digitized images and inverse-intensity (bones black) images, Sheline et al (38) found that inverse-intensity image can have some benefits in lesion recognition.…”
Section: Improving Techniquesmentioning
confidence: 99%
“…By comparing the ability to identify pulmonary nodules on conventional plain chest radiographs, standard (bones white) digitized images and inverse-intensity (bones black) images, Sheline et al (38) found that inverse-intensity image can have some benefits in lesion recognition.…”
Section: Improving Techniquesmentioning
confidence: 99%
“…11 Conversely, inverse grayscale can make tubes 12 and soft tissue abnormalities 13 easier to detect but at the expense of the more familiar black on white x-ray pattern. 14 Furthermore, some investigators showed that masses can be better detected 15 because inverse grayscale provides a``second-look'' where the radiologist has another chance to pick up subtle tumors. Problems with excessive reading room ambient light or re¯ective glare on the monitor screen can be minimized by the inverse grayscale images.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] The use of image processing to enhance image information content is also being investigated. [7][8][9] Even if diagnostic performance with PACS displays were equal to (or better than) that achieved with film, it does not by itself guarantee that physician performance (and possibly, patient care) will be unchanged.…”
mentioning
confidence: 99%